Gated Estates and an Evaluation of Gating Forms in Krakow’s Podgórze District - Ptak, Joanna; Serafin, Piotr (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2017)
The rising number of gated estates, usually created as autonomic units and which stand out from their surroundings, contributes to the fragmentation of the urban environment and has been roundly criticised. The article identifies the causes and effects of creating gated estates in Polish cities, as well as the forms of their gating and opinions about them. The analysis was conducted in the Podgórze district, which has a significant number of such estates. The study confirms the critical views that have been expressed elsewhere in the subject literature about gated estates. However, it is the form of gating, or fencing, that plays an important role in the arrangement of space, which in fact creates public opinion. The form of gating can influence not only the relationships inside gated areas, but also the relationship inhabitants have with the external environment. This leads to the conclusion that each of them should be analyzed separately.